The multimodal display of rattlesnakes is a deterring signal that works best with sympatric species - Océane Da Cunha; Joshua J. Mead; L. Miles Horne (PLoS ONE, 2026)
The rattlesnake rattle is one of the most iconic communication signals in nature, yet its evolutionary function remains poorly understood. To test the long-standing hypothesis that the defensive display of rattlesnakes acts as a deterrent, we developed a 3D-printed robotic rattlesnake capable of displaying the multimodal sensory stimulus produced by a rattlesnake. This robot was presented to 38 species of zoo-housed animals in a series of behavioral trials. Animals displayed aversive response to the signal, suggesting that this multimodal display functions as a deimatic signal by triggering reflexive avoidance response. Sympatric species exhibited even stronger fear response to the display, suggesting an evolved, innate fear to the signal. These results offer insights into how complex antipredator signals can originate and diversify in the animal kingdom.